Sensitive imaging of intact microvessels in vivo with synchrotron radiation - Wang, Feixiang (IUCrJ, 2020)
Early stages of diseases, including stroke, hypertension, angiogenesis of tumours, spinal cord injuries, etc., are closely associated with the lesions of microvasculature. Rodent models of human vascular diseases are extensively used for the preclinical investigation of the disease evolution and therapy with synchrotron radiation. Therefore, non-invasive and in vivo X-ray imaging with high sensitivity and clarity is desperately needed to visualize the microvessels in live-animal models. Contrast agent is essential for the in vivo X-ray imaging of vessels and angiomatous tissue. Because of the non-rigid motion of adjacent tissues, the short circulation time and the intermittent flow of contrast agents in vessels, it is a great challenge for the traditional X-ray imaging methods to achieve well defined images of microvessels in vivo. In this article, move contrast X-ray imaging (MCXI) based on high-brightness synchrotron radiation is developed to overcome the intrinsic defects in conventional methods. Experiments with live rodents demonstrate the practicability of the MCXI method for sensitive and intact imaging of microvessels in vivo.